Formação inicial de professores de química: discursos, saberes e práticas - Corrêa, Roberta Guimarães (Universidade Federal de São Carlos, 2015)
Currently, the academic community and teachers formation courses are still living a period of transition between educational performance models that are supported by regulations, such as the resolution CNE/CP n° 01/2002, which features the National Curriculum Guidelines for the Basic Education Teachers Formation. In these documents and also in research carried out, we try to overcome the formation focused on technical rationality. Searching the formation of a professional who is the author of your own practice and master and specialized skills. Considering this formation model, studies of teacher formation have as issues of interest to identity the teacher knowledge, pedagogical practice, professionalism, autonomy, among others. The formation process, which is for all teacher s professional life and even before it, has in degree courses an important moment of contact with the knowledge, practices and the constitution of the teacher identity. Therefore, questions about the initial formation, the knowledge and the desired professional profile on degree courses in Chemistry deserve further investigation. In this qualitative research, higher education institutions of the State of São Paulo were researched in order to investigate and analyze the initial formation of Chemistry teachers in Chemistry Degree courses. This picture of reality was subjected to a critical analysis supported by references that formed the basis for the discussion of possible paths to the initial formation of Chemistry teachers. For the analysis, data were collected on the sites of the institutions to known the profile of professionals in formation and on playing field. Also collections were made in seven institutions with teachers trainers and undergraduates. The analyzes point to a course profile which, despite being to form teachers, has as major goal the training of a skilled professional for the work in a diverse market, with little emphasis on teaching. Specific knowledge of Chemistry is prioritized by both undergraduates and by trainers who in turn give little attention to the pedagogical knowledge. A formation model is presented and discussed in order to contribute to the improvement of undergraduate courses in chemistry.
Initial formation of chemistry teachers: speeches, knowledge and practice
Keywords: Professores - formação; Formação inicial; Química; Licenciatura; CIENCIAS EXATAS E DA TERRA::QUIMICA